Periumbilical Pain with Radiation to Both Legs Following Tarantula Bite; a Case Report - Pouraghaei, Mahboob; Shams Vahdati, Samad; Mashhadi, Ibrahim; Mahmoudieh, Taranoom (Archives of Academic Emergency Medicine, 2018)
Tarantulas have recently become as pets in most parts of the world that increased the probability of encountering emergency physicians with patients hurt with these spiders. Their attacks usually do not cause general manifestation, however there are some case reports in this regard. Here, a 40-year-old man was reported who was referred to the emergency department with severe periumbilical pain that radiated to both legs and diagnosed as a victim of tarantula bite. Such symptoms usually are belonging to other spiders like Black Widow spider, but it seems that tarantula can mimic them in some cases, too.